Biphasic Orthodontic Treatment for Severe Class III Malocclusion Using Orthopedics and Orthodontic Camouflage: A Case Report - , Yure Gonçalves Gusmão, Anna Marina Teixeira Rodrigues Neri, Marco Túllio Becheleni, Paulo César de Oliveira, Thiago Fonseca Silva (Archives of Current Research International, 2024)
Class III malocclusion in growing patients is one of the most challenging problems in orthodontics in terms of diagnosis, prognosis and treatment, mainly due to the unpredictability of the growth pattern in these patients. At this stage, malocclusion can be corrected in a variety of ways, depending on the degree of discrepancy and the pattern of malocclusion. Thus, the objective of this study was to demonstrate the importance of early treatment of Class III malocclusion in a child treated by using interceptive and corrective orthodontic treatment, first with an orthopedic approach associated with the rapid palatal expansion and Petit mask, and after with conventional orthodontic camouflage therapy using corrective fixed appliances and premolars extractions. We conclude that early interception through orthodontic mechanics and facial orthopedics proved to be an effective treatment alternative, yielding satisfactory and stable aesthetic-functional results, along with the patient’s satisfaction in utilizing orthodontic camouflage instead of undergoing orthognathic surgery.